The Effect of Grain Size and Applied Stress to The Mechanical Properties of Low Carbon Steel due to Hydrogen Embrittlement - HADI (NIM 13704048), NURUL
Hydrogen embrittlement is a phenomenon that decrease the ductility and toughness of a steel. Commonly low carbon steel, HSLA and Titanium are susceptible to hydrogen. In application low carbon steel is used as a material for piping that are usually protected by using electroplating and catodic protection that will introduce hydrogen in the process. This research is to observe the effect of grain size and applied stress to the mechanical properties of low carbon steel due to hydrogen embrittlement. To simulate the hydrogen embrittlement process, a charging system was devised by using 0.5 M H2SO4 for 3 hours with a current density of 210 mA/cm2. To observe the mechanical properties after experiment, the samples were tested using a tensile test machine and fracture surface were studied by using optical microscope. It is found that low carbon steel with grain size 15.9 um (ASTM grain size 9) has a higher susceptibility to hydrogen charging than with a sample with grain size 26.3 um (ASTM grain size 7.5). It is shown by the decrease of their toughness wich are 64.5 % and 45.6 %. Sample with 200 MPa constantly applied stress during charging has reduced its toughness to 72.1 %.